2019
DOI: 10.1002/ece3.5121
|View full text |Cite
|
Sign up to set email alerts
|

Bats in a changing landscape: Linking occupancy and traits of a diverse montane bat community to fire regime

Abstract: Wildfires are increasing in incidence and severity across coniferous forests of the western United States, leading to changes in forest structure and wildlife habitats. Knowledge of how species respond to fire‐driven habitat changes in these landscapes is limited and generally disconnected from our understanding of adaptations that underpin responses to fire. We aimed to investigate drivers of occupancy of a diverse bat community in a fire‐altered landscape, while identifying functional trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 85 publications
3
39
1
Order By: Relevance
“…In contrast, assessments of fire severity on bats are more limited in number and ability to infer species-level effects. A concurrent study conducted in northern Sierra Nevada forests found bat functional traits associated with open areas were positively correlated with high-severity fire and fire frequency, whereas traits associated with habitat clutter tolerance were negatively correlated with such fire characteristics 7 . Similarly, a previous study in southern Sierra Nevada mixed conifer forests found higher activity rates of small-bodied species within high-severity areas 8 , and a study in Idaho forests found that overall bat activity was higher in high-severity areas than unburned areas 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, assessments of fire severity on bats are more limited in number and ability to infer species-level effects. A concurrent study conducted in northern Sierra Nevada forests found bat functional traits associated with open areas were positively correlated with high-severity fire and fire frequency, whereas traits associated with habitat clutter tolerance were negatively correlated with such fire characteristics 7 . Similarly, a previous study in southern Sierra Nevada mixed conifer forests found higher activity rates of small-bodied species within high-severity areas 8 , and a study in Idaho forests found that overall bat activity was higher in high-severity areas than unburned areas 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, future work should build on the findings presented here by exploring the relative importance of fire effects on foraging clutter, roost availability in the form of snag creation, and alterations to prey communities 43 . Habitat resources and bat occupancy also likely change with post-fire succession 7 and a more complete understanding of these temporal dynamics would improve our ability to conserve bats across landscapes with complex fire histories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insectivorous bats are highly mobile predators that respond to forest structure and fire based on their diverse call and morphological traits (Schnitzler et al 2003;Denzinger and Schnitzler 2013;Blakey et al 2019). At fine spatial scales (B 500 m), bats adapted to open areas and many edge-adapted species benefit from higher burn severity and more frequent fire (Armitage and Ober 2012;Buchalski et al 2013;Inkster-Draper et al 2013;Cox et al 2016;Blakey et al 2019;Steel et al 2019). Bats also use edges and openings created by timber harvest (Law et al 2016b and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…We propose the 2019-2020 res will have signi cant population impacts on grey-headed ying foxes through substantial reduction in habitat and feeding resources at speci c roosts. Although there are no other studies of ying fox responses to res, studies of other bat species have shown that res impact populations through the alteration of foraging and roosting habitat 50,51,52 , and other Australian bats (non-Pteropus) have been shown to decrease activity in local areas in the months following bush res and up to one-year after major res 29,52 . The anomalous season of 2019-2020 bush res signi cantly impacted foraging resources for grey-headed ying foxes, which will alter their feeding behavior, and in turn, could delay recovery of Eucalypts that bene t from their pollination.…”
Section: Reductions In Winter Foraging Habitats Have Been Associated mentioning
confidence: 99%